Functional Outcomes by Age for Inpatient Cancer Rehabilitation: A Retrospective Chart Review. (June 2013) - Hunter, Elizabeth G.; Baltisberger, Julie
Cancer-related impairments result in disabilities similar to those typically encountered in inpatient rehabilitation settings; however, the use of rehabilitation services by cancer survivors is low. This is particularly important for older adults as they are at higher risk for cancer. This retrospective study collected data from medical records from 215 charts of patients admitted to an inpatient physical rehabilitation hospital, within a 5-year period, with a primary diagnosis of cancer. Mean age was 61 years ( SD = 15.7) for 109 (51%) females and 106 (49%) males. Regardless of age, patients achieved significant functional improvement, as shown by their FIM scores ( t = 23.06, p < .0001), from admission to discharge. The results have several important implications related to cancer survivorship among older adults. With a push toward aging in place, maintaining optimal physical functioning is crucial. Physical rehabilitation benefited the functional outcomes of this group of cancer survivors regardless of age.